Innovative integration of sofcs as range extenders: Enhancing range and performancein electric vehicles/ Mohammad Fikrey Roslan ... [et al.] - Roslan, Mohammad Fikrey; Abd Karim, Rafidah; Taufiq Musa, Maryam; Kandong, Sapiyan (2023)
This abstract introduces a revolutionary design that blends SOFCs with EVs to improve range and performance. SOFCs as range extenders in EVs provide an innovative solution to battery technology's constraints and will transform sustainable transportation. SOFCs generate power more efficiently than EV batteries. SOFCs can power EVs continuously and sustainably by utilizing their high efficiency. A major issue with EVs is their limited range, but this invention extends it. EV performance improves with SOFC range extenders. SOFCs' increased energy density and power-to-weight ratio boost acceleration and performance, improving drive quality while protecting the environment. This novel technique addresses charging infrastructure. SOFCs utilise hydrogen or natural gas, reducing the need for large charging networks. This simplifies refuelling and allows localized energy generation, lowering grid pressure. This integration shows great potential, but SOFC system cost, size, and durability remain issues. Research and development are needed to improve performance, lower production costs, and maintain long-term dependability under dynamic operating circumstances. In conclusion, using SOFCs as range extenders in EVs offers a unique chance to improve range, performance, and practicality. This innovative strategy might revolutionise the transportation sector and accelerate the worldwide transition to sustainable and eco-friendly travel. SOFCs and EVs will provide a cleaner, more efficient, and greener transportation future with additional developments and judicious investments.